Puboplasty as an integral step in massive weight loss abdominal contouring: a retrospective assessment of results, stability, and patients' satisfaction. Issue 6 (1st December 2022) - Simone, Pierfranco; Savani, Luca; Marchica, Paolo; Persichetti, Paolo
Abstract: Ex-obese patients complain about abdomen and pubis deformities following massive weight loss, due to skin and soft tissue redundancy. Abdominoplasty is often the first corrective procedure performed, but residual mons pubis deformities may impair the final outcome, thus concomitant correction becomes necessary. Sixty patients were treated by the same surgeon between 2008 and 2018, 30 of them receiving only standard umbilical transposition abdominoplasty (A group), and 30 having concurrent monsplasty (AM group), namely skin excess removal, pubic suspension and skin redistribution following superolateral vectors, re-establishment of superficial fascia continuity, with or without liposuction. Retrospective comparison of the two groups included: a subjective evaluation through administration of questionnaires (BODY-Q TM, a questionnaire assessing functional and aesthetic improvements after surgery, a questionnaire assessing the overall satisfaction), and an objective evaluation of pre- and post-operative pictures to estimate mons pubis suspension and result stability. Four minor complications were recorded: 1 wound dehiscence in A group, 3 seromas in AM group. All measured outcomes were higher in AM group, with statistically significant difference ( p < 0.05) in almost all the questionnaire and BODY-Q TM items, and the photographic assessment confirmed higher degree of mons pubis suspension and superior result stability in AM group. We presented a standardized approach to mons pubis reshaping during abdominoplasty, through a straightforward, safe and quick procedure. Our experience supports the significance of the concomitant correction of abdominal and mons pubis deformities, improving the results of the surgery from both a subjective and objective point of view.